Vanilla planifolia, the first Mesoamerican orchid illustrated, and notes on the de la Cruz-Badiano Codex - Gómez, Luis Diego (Universidad de Costa Rica, 2008)
The Codex Barberini lat. 241 or Codex Badianus is a manuscript by Martín de la Cruz, entitled Libellus Medicinalibus Indorum Herbis and the first New World herbal, written in 1552. It includes 249 medicinal plants of which only 184 are illustrated. Among the plants depicted is tlilxochitl which is the Nahuatl name, even to this day, for Vanilla planifolia Andrews. Thus, the illustration of that plant in the Codex constitutes the first illustration of a Mesoamerican orchid done for European readers and antedates the publication of the genus and its species by two centuries. Some new historical aspects of the Codex are presented.